Consistent higher order σ GG → h $$ σ \left(\mathcal{GG}→ h\right) $$ , Γ h → GG $$ Γ \left(h→ \mathcal{GG}\right) $$ and Γ(h → γγ) in geoSMEFT - Tyler Corbett; Adam Martin; Michael Trott (Journal of High Energy Physics, 2021)
Abstract We report consistent results for Γ(h → γγ), σ GG → h $$ σ \left(\mathcal{GG}→ h\right) $$ and Γ h → GG $$ Γ \left(h→ \mathcal{GG}\right) $$ in the Standard Model Effective Field Theory (SMEFT) perturbing the SM by corrections O υ ¯ T 2 / 16 π 2 Λ 2 $$ \mathcal{O}\left({\overline{υ}}_T^2/16π^2Λ^2\right) $$ in the Background Field Method (BFM) approach to gauge fixing, and to O υ ¯ T 4 / Λ 4 $$ \mathcal{O}\left({\overline{υ}}_T^4/Λ^4\right) $$ using the geometric formulation of the SMEFT. We combine and modify recent results in the literature into a complete set of consistent results, uniforming conventions, and simultaneously complete the one loop results for these processes in the BFM. We emphasize calculational scheme dependence present across these processes, and how the operator and loop expansions are not independent beyond leading order. We illustrate several cross checks of consistency in the results.